2013
DOI: 10.3109/00365521.2012.758773
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of mucosal cytokine gene expression levels predicts long-term remission after discontinuation of anti-TNF therapy in Crohn's disease

Abstract: Normalization of mucosal gene expression of cytokines after anti-TNF therapy does not occur in all patients with healed mucosa as judged by endoscopy. Normalization of TNF and/or IL17A expression predicts long-term remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 40 publications
7
33
0
Order By: Relevance
“…47 Although it requires further investigation, it is important to acknowledge that recent studies of anti-TNF cessation in patients with deep remission (including some in radiological and even histological remission) have roughly similar relapse rates, with approximately 50% of patients experiencing a relapse after variable periods of follow-up. 39,57,[62][63][64] After stopping therapy, it is possible that an individual's particular disease course will eventually manifest and follow its natural trajectory. 75 Therapeutic drug monitoring offers a promising avenue to identify candidates for de-escalation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…47 Although it requires further investigation, it is important to acknowledge that recent studies of anti-TNF cessation in patients with deep remission (including some in radiological and even histological remission) have roughly similar relapse rates, with approximately 50% of patients experiencing a relapse after variable periods of follow-up. 39,57,[62][63][64] After stopping therapy, it is possible that an individual's particular disease course will eventually manifest and follow its natural trajectory. 75 Therapeutic drug monitoring offers a promising avenue to identify candidates for de-escalation.…”
Section: Discussionmentioning
confidence: 99%
“…Radiological healing as assessed by magnetic resonance imaging was also shown in one study. 62 Rismo et al 63 reported higher rates of relapse (52% at 6 months and 74% at 12 months), potentially relating to short treatment duration before withdrawal. The other studies reported relapse rates of 18% at 6 months, 57 22% to 41% at 12 months, 57,62 47% to 49% at 24 months, 57,62 and 50% at 36 months, 39 very similar to that of those withdrawn while in clinical remission.…”
Section: De-escalation Of Anti-tnf In CDmentioning
confidence: 99%
See 2 more Smart Citations
“…This conclusion comes in part from the findings that CD patients have a higher number of circulating IL-17+ cells33 and from a study by Rismo et al,34 which showed that increased messenger (m) RNA expression of tumor necrosis factor (TNF) and IL17A in healed mucosa significantly increased the risk of relapse (hazard ratio [HR] = 3.4, P = 0.03, sensitivity 80%, specificity 38% and HR = 4.1, P = 0.008, sensitivity 81%, specificity 61%, respectively).…”
Section: Introductionmentioning
confidence: 97%